Integration of Local Wisdom and Digital Literacy in Social Studies Learning as a Strategy to Strengthen Students' Civic Responsibility - Ilham Mufid; Yuni Candra Wibowo; Siti Nurhaliza (Gema Cendekia Institute, 2026)
The rapid advancement of digital technology has transformed the ways students access information, communicate, and participate in social life. While these developments create new opportunities for learning and civic engagement, they also present challenges related to misinformation, unethical online behavior, declining social sensitivity, and weakening civic responsibility. In this context, Social Studies learning plays a strategic role in developing students’ citizenship competencies. This study aims to analyze the integration of local wisdom and digital literacy in Social Studies learning as a strategy for strengthening students’ civic responsibility. Employing a quantitative approach with an explanatory survey design, the study examined the relationships among local wisdom integration, digital literacy, and civic responsibility among junior high school students. Data were collected through questionnaires, observations, documentation, and interviews and analyzed using descriptive and inferential statistical techniques, including multiple regression analysis. The findings indicate that the integration of local wisdom and digital literacy contributes positively to the development of civic responsibility. Local wisdom provides cultural values that encourage social awareness, mutual cooperation, tolerance, and responsibility, while digital literacy equips students with the skills needed to access, evaluate, and utilize information ethically and responsibly. The combination of these dimensions creates meaningful learning experiences that enable students to connect local cultural values with contemporary social realities. The study concludes that integrating local wisdom and digital literacy within Social Studies learning can serve as an effective educational strategy for fostering civic awareness, responsible participation, and ethical behavior among students in the digital era. The findings offer practical implications for the development of contextual, culturally responsive, and digitally oriented citizenship education.